Effect Of Giving Avocado (Persea americana M.) Juice on MDA and TNF-α Levels - Effendi, Anita Putri; Trisnadi, Setyo; Isradji, Israhnanto (Asian Journal of Health and Applied Sciences, 2023)
A Cigarette is one of the free oxygen radicals that interfere with a free radical’s balance and antioxidant in the body. It involves oxidative stress. Oxidative stress involves a failure system that triggers an inflammation response in endothelial class blood vessels that have pinned exiting the inflammation reaction in the form of cytokines, especially TNF-α. It functioned to know the effect of awarding avocado juice to MDA and TNF-α. This research used the experimental laboratory method that approached a post-test-only control group design. The subject of this research used 20 Wister rats, which kind of inclusion. It is shared in 4 sections as random services. Such as K1, K2, K3 and K4. K1 has given a standard weft. It has been done without a smoking display. Meanwhile, K2 has given a standard weft that has used a smoking display for 14 days. K3 and K4 have been given avocado juice doses. It was as much as 2,7g/200g weight/day and 54g/200g weight/day. On the fifth day, the specimen has taken the blood. It could know the results of MDA and Tnf-a. The data analysis used the normality test by Shapiro Wilk, homogeneity, Levene, and one-way ANOVA test. The result of this research has the highest rate. The highest rate was K2. It could be proven for the One-Way Anova MDA and Tnf rate test. It showed a significant difference between categories, which is p=0,000 scores. The conclusion of this research has been giving avocado juice with 2,7g/200g weight/day and 5,4g/200g weight/day. Then, it could reduce the MDA and Tnf-a rate on the Wistar rat. It has been since the smoking display.